Diagnostic value of lung ultrasound B-lines for evaluating left ventricular filling pressure - Takahiro Sakamoto; Toshihiko Asanuma; Hiroyuki Sasaki; Hiroshi Kawahara; Kazuhiko Uchida; Akihiro Endo; Hiroyuki Yoshitomi; Kazuaki Tanabe (Cardiovascular Ultrasound)
Abstract Background The assessment of left ventricular (LV) diastolic function based on the American Society of Echocardiography and the European Association of Cardiovascular Imaging (ASE/EACVI) guidelines requires measurement of several echocardiographic indices. However, these assessments often yield inconclusive results owing to the absence of measurable parameters. Multiple B-lines on lung ultrasound have been proposed as a method for evaluating pulmonary congestion. We aimed to evaluate the association between B-lines and LV diastolic function and to examine whether B-lines show potential as an alternative to conventional indices for assessing LV diastolic function. Methods This prospective study included 172 patients with pre-heart failure (HF) or HF. We investigated (i) the relationship between B-lines and LV diastolic function using echocardiography, (ii) the diagnostic accuracy of B-lines compared to echocardiography indices for estimating LV filling pressures and (iii) the relationship between B-lines and risk of hospitalisation for HF. Results Among patients for whom the ASE/EACVI guideline algorithm for LV diastolic dysfunction was available (n = 89), the number of B-lines typically increased with the severity of diastolic dysfunction grade. In patients who underwent left heart catheterisation (n = 20), the LV filling pressure was significantly correlated with B-lines (r = 0.690, P < 0.001). The diagnostic accuracy of B-lines for detecting high LV filling pressure was comparable to that of tricuspid regurgitation peak gradient (TRPG). When TRPG was replaced with B-lines to diagnose grade II or III diastolic dysfunction using the ASE/ESCVI algorithm, sensitivity remained comparable (0.80); however, specificity improved (0.80 vs. 0.50). In patients who underwent lung ultrasound while they were hemodynamically stable and were followed up for prognosis (median, 730 days; n = 75), 14 hospitalisations for HF were observed. Kaplan–Meier analysis revealed that the high B-line group had a significantly higher incidence of hospitalisation events for HF (P = 0.036, log-rank test). Conclusion B-lines have shown potential as an alternative to conventional indices for assessing LV diastolic dysfunction. Graphical Abstract